Numerical simulation of the hydrodynamics and mass transfer in the growth of KH2PO4 crystal through a frustum platform. (August 2019) - Wang, P.F.; Li, M.W.; Liu, H.
Highlights: 3-D unsteady numerical simulations of flow and mass transfer are carried out. The introduction of frustum eliminates the vortices near the lower prismatic face. The increases of rotation rate and crystal size will do good for the pyramidal face. Experimental results confirm that frustum platform benefits crystal quality. Abstract: A frustum is added to the platform used in the rapid growth of the potassium dihydrogen phosphate crystal on point seed, aiming at improving the supersaturation distribution on crystal surfaces. To evaluate the modification, numerical simulations of the hydrodynamics and mass transfer involved in the aqueous solution growth of KH2 PO4 with the new platform have been performed. The variations of surface supersaturation with frustum inclination, rotation rate and crystal size are analyzed. The results show that the existence of frustum eliminates the low-supersaturation area on the lower prismatic face and greatly promotes the supersaturation distribution uniformity. Moreover, the increases of rotation rate and crystal size not only help to improve the supersaturation distribution on the prismatic face, but also substantially reduce the low-supersaturation area on the pyramidal surface. Performance tests of small size crystals grown with ordinary and frustum platform confirms that frustum platform benefits crystal quality. Under optimum design and growth conditions, the simple frustum holds the potential for considerably improving the quality of large size crystal.